1979
DOI: 10.1002/star.19790311002
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Corn Starch and Fine Flour by Acid and Gamma Irradiation. Part 1. Chemical Investigation of the Modified Products

Abstract: Fine flour from corn and the isolated starch were dextrinized in the presence of acid and irradiated with y‐rays. Starch irradiated with high doses of y‐rays was highly modified while fine flour was less affected. The irradiated starch was reduced with sodium borohydride and then hydrolysed. Erythritol and other compounds were identified in the hydrolysate. It was concluded that the C2‐C3 bonds in the intermediate glucose units are probably broken by irradiation. Such hypothesis was confirmed by periodate oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 7 publications
2
7
0
2
Order By: Relevance
“…Increased carboxyl content in starch occurred due to the degradation of starch by gamma irradiation, which causes the generation and transformation of free radicals and follows the low‐molecular products with the number of carboxylic acids and aldehydes (Sharpatyi, ). This variation in the carboxyl content in irradiated starches could be due to the formation of acids such as formic, acetic, pyruvic and glucuronic acids by the action of free radicals (Ghali et al ., ). These results were comparable with other studies (Chung & Liu, ; Ashwar et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Increased carboxyl content in starch occurred due to the degradation of starch by gamma irradiation, which causes the generation and transformation of free radicals and follows the low‐molecular products with the number of carboxylic acids and aldehydes (Sharpatyi, ). This variation in the carboxyl content in irradiated starches could be due to the formation of acids such as formic, acetic, pyruvic and glucuronic acids by the action of free radicals (Ghali et al ., ). These results were comparable with other studies (Chung & Liu, ; Ashwar et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Abd Allah, Foda, and El Saadany (1974) observed substantial increase in the production of formic acid in irradiated wheat starch. Formic, pyruvic, acetic and glucuronic acids are formed during irradiation of starch (Ghali, Ibrahim, Gabr, & Aziz, 1979) which therefore could be responsible, not only for the elevation in carboxyl content levels with irradiation dose but also for reduction in pH values of all starch samples. Similar findings were reported by Chung, Hoover, and Liu (2009) and Chung and Liu (2010) with irradiated corn and bean starch respectively.…”
Section: Moisture Carboxyl Content and Phmentioning
confidence: 99%
“…The radiation degradation of starch is initiated by the generation and transformation of free radicals and follows the low-molecular products with the number of carboxylic acids and aldehydes [23]. Ghali et al [24] reported that formic, acetic, pyruvic and glucuronic acids were formed during irradiation of starch. Therefore, the main degradation products formed during irradiation of native starch were carboxylic acids, which resulted in an increase in carboxyl content and a decrease in pH value of all starch samples.…”
Section: Carboxyl Contentmentioning
confidence: 99%